Zinc-Dependent Protection of Tobacco and Rice Cells From Aluminum-Induced Superoxide-Mediated Cytotoxicity - Lin, Cun; Hara, Ayaka; Comparini, Diego; Bouteau, François; Kawano, Tomonori (Frontiers in Plant Science, 2015)
Al3+ toxicity in growing plants is considered as one of the major factors limiting the production of crops on acidic soils worldwide. In the last 15 years, it has been proposed that Al3+ toxicity are mediated with distortion of the cellular signaling mechanisms such as calcium signaling pathways, and production of cytotoxic reactive oxygen species (ROS) causing oxidative damages. On the other hand, zinc is normally present in plants at high concentrations and its deficiency is one of the most widespread micronutrient deficiencies in plants. Earlier studies suggested that lack of zinc often results in ROS-mediated oxidative damage to plant cells. Previously, inhibitory action of Zn2+ against lanthanide-induced superoxide generation in tobacco cells have been reported, suggesting that Zn2+ interferes with the cation-induced ROS production via stimulation of NADPH oxidase. In the present study, the effect of Zn2+ on Al3+-induced superoxide generation in the cell suspension cultures of tobacco (Nicotiana tabacum L., cell-line, BY-2) and rice (Oryza sativa L., cv. Nipponbare), was examined. The Zn2+-dependent inhibition of the Al3+-induced oxidative burst was observed in both model cells selected from the monocots and dicots (rice and tobacco), suggesting that this phenomenon (Al3+/Zn2+ interaction) can be preserved in higher plants. Subsequently induced cell death in tobacco cells was analyzed by lethal cell staining with Evans blue. Obtained results indicated that presence of Zn2+ at physiological concentrations can protect the cells by preventing the Al3+-induced superoxide generation and cell death. Furthermore, the regulation of the Ca2+ signaling, i.e. change in the cytosolic Ca2+ ion concentration, and the cross-talks among the elements which participate in the pathway were further explored.